ON STAUDE S NEW GENERIC NAMES FOR AGARICS - DONK, M. A. (Research Center for Biology, 1954)
The author concludes that the generic names for agarics first introduced by Staude (1857) have been validly published.When I drew attention to Staudes forgotten